การบริหารงานวิชาการของผู้บริหารโรงเรียน สังกัดสำนักงานการศึกษาเอกชนจังหวัดยะลา - Yenpiam, phayungsri (Al-HIKMAH Journal, 2022)
Abstract The objectives of this research were 1) to study the level of academic administration of school administrators. Under the Yala Provincial Office of Private Education 2) to study the level of academic administration of school administrators Under the Yala Provincial Office of Private Education and 3) to compile recommendations on academic administration of school administrators. Under the Yala Provincial Office of Private Education The sample consisted of 252 teachers of schools affiliated with the Yala Provincial Office of Private Education, which were obtained by randomly stratified by landscape. The tool used is Estimation questionnaire Analysis of statistical data, percentage, mean Standard deviation, t-test , F -test by one-way analysis of variance and paired comparison. by the way of the chef The results of independent research found that Level of academic administration of school administrators Under the Yala Provincial Office of Private Education The overall picture is at a high level. Comparison of the level of academic administration of school administrators classified by sex, age , found that the overall and each aspect were not different, classified by working experience. Overview and aspects The difference was statistically significant at the 0.05 level. The pairs that differed were teachers with less than 5 years of work experience, opinions on guidance and development of internal quality assurance systems and educational measures. Varies with teachers with 10+ years of work experience and classified by school size. Overview and aspects There was a significant difference at the 0.05 level in all aspects except for promoting the community to be academically strong. no different Recommendation processing results Academic administration of school administrators Under the Yala Provincial Office of Private Education, namely , administrators should prepare local learning content of the school for preparation of additional courses , and should supervise and supervise the subject matter. Regularly arrange activities that are in line with the learners’ interests and aptitudes. The management should support the organization of activities for Learners learn from real experiences. Emphasis should be given to teachers to have measurements, evaluations, comparisons, transfers, and learning reforms using research processes as a priority. Support the exploration of learning resources from outside and inside the school Support the implementation of guidance and support for students Support the development of the community in accordance with the problems and needs of the community, strengthen the relationship between the school and the community, as well as various organizations. Executives should consider the content. the language of the book The textbook is theoretically correct and up-to-date. Encourage teachers to develop media and teaching innovations Always keep up with the changes Keywords : Academic administration ; private school administrators ; teacher